Geographical information systems theory, applications and management : second International Conference, GISTAM 2016, Rome, Italy, April 26-27, 2016, Revised selected papers /: second International Conference, GISTAM 2016, Rome, Italy, April 26-27, 2016, Revised selected papers. (2017) - Unknown
No abstract available